Comportamiento de Polylepis racemosa en vivero mediante propagación vegetativa utilizando cuatro longitudes de estacas en platabandas a nivel en tres diferentes pisos altitudinales Cayambe 2008 - Gualavisí Quimbiamba, Luis Galo (2008)
The yagual species are (Polylepis sp.) found from 3,000 to 3,200 msnm decreasing of species number at higher and lower sites; this is the most vulnerable habitats from the High lands because anthropogenic strong pressure, the increase agricultural border, also to increase free tree areas for pasturage, the use such as wood has been one the most devastating causes in the destruction of our uplands. The plants production of Polylepis is monetary source for nursery people; this specie has been utilized in reforestation programs, by government and non-government entities. This work was taken performed in three altitude floors at (2867, 3103 and 3365 m.s.n.m), for to knowing the behaviour of Polylepis racemosa in nursery using vegetative propagation with four sticks long in level floor.